2016
DOI: 10.1080/07373937.2015.1081931
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effects of three conventional drying methods on the lipid oxidation, fatty acids composition, and antioxidant activities of walnut ( Juglans regia L.)

Abstract: Three walnut (Juglans regia L.) drying methods (sun drying, direct oven drying, and intermittent oven drying) were employed, and the consequent changes in lipid oxidation attributes, such as acid value (AV), peroxide value (POV), saponification value (SV), fatty acid composition, antioxidant activity (including reducing power, superoxide anion scavenging activity, 1,1-diphenyl-2-picrylhydrazyl free radical scavenging activity [DPPH], lipoxygenase (LOX) activity, total phenols content (TPC), and total flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 27 publications
(30 reference statements)
6
38
1
1
Order By: Relevance
“…The pre‐treatment of oilseeds prior to extraction process may affect total oil yield and its quality . Pre‐treatments can be used to rupture the cell wall structures of oilseeds, enhancing the release of oil from the cellular bodies and increasing extraction yield .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The pre‐treatment of oilseeds prior to extraction process may affect total oil yield and its quality . Pre‐treatments can be used to rupture the cell wall structures of oilseeds, enhancing the release of oil from the cellular bodies and increasing extraction yield .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al, who studied the effects of different drying methods (ie, oven‐drying, freeze‐drying, vacuum‐drying, and microwave‐drying) on the extraction rate and qualities of flaxseed oil, reported that microwave‐drying and freeze‐drying have the highest extraction rates and yields (46.36% and 46.16% vs 33.90%) compared to native flaxseed. Qu et al studied the effects of oven‐drying and sun‐drying on walnut oil oxidation and reported that oven‐drying is a promising method for walnut drying. Freeze‐drying has been an attractive method for extending the shelf life of food, whereas oven‐drying has been used in the food industry .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations